Preparation method and application of low carbon aluminum alloy

By using surface grafting treated boron nitride synergist and multi-stage filtration slag treatment technology in recycled aluminum alloys, the problem of the influence of iron impurities in recycled aluminum alloys is solved, and a low-carbon aluminum alloy with good mechanical properties is prepared, which is suitable for automotive structural parts and reduces the quality and energy consumption of the whole vehicle.

CN119320889BActive Publication Date: 2025-03-28YUNNAN HONGBANG NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411864198.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing recycled aluminum alloy has high iron impurities, which affects the performance of the material, and increases the risk of surface cracking during high-speed extrusion processing, limiting its application range.

Method used

Boron nitride treated with surface grafting is used as a synergist. By improving the compatibility of the synergist and the aluminum alloy matrix, it is uniformly dispersed in the aluminum alloy system, and multi-stage filtration slag treatment is carried out to remove impurities to prepare a low-carbon aluminum alloy.

Benefits of technology

It improves the tensile strength, yield strength and ductility of low-carbon aluminum alloys, meets the material performance requirements of automotive structural parts, reduces the quality and energy consumption of the whole vehicle, and increases a single range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of recycled aluminum alloys, in particular to a preparation method and application of low-carbon aluminum alloys. The preparation method of low-carbon aluminum alloys is as follows: first, aluminum liquid A is prepared; then, aluminum liquid A is cooled to 780-800°C, a synergist is added, stirred and evenly smelted for 2-3 hours to obtain aluminum liquid B; then, aluminum liquid B is stirred and blown to remove hydrogen and impurities to obtain aluminum liquid C; finally, the obtained aluminum liquid C is subjected to a 10-15min slag treatment to obtain a finished aluminum alloy melt, and the finished aluminum alloy melt is cast + T6 heat treatment to obtain a low-carbon aluminum alloy. The low-carbon aluminum alloy prepared in the present invention has good tensile strength, yield strength and ductility, can meet the material performance requirements of automotive structural parts, reduce the quality of the whole vehicle and the energy consumption of the whole vehicle operation, and can increase the single voyage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycled aluminum alloys, and in particular to a preparation method and application of a low-carbon aluminum alloy. Background Art

[0002] At present, with the low-carbon emission requirements for cast aluminum alloys, in order to reduce carbon emissions in the aluminum alloy manufacturing process, it is necessary to use recycled aluminum as raw material to produce cast aluminum alloys. However, the iron content in most recycled aluminum is >1%, and iron impurities generally exist in the form of coarse needle-shaped brittle intermetallic compounds in aluminum alloys, which will seriously affect the various properties of recycled aluminum alloys and increase the risk of surface cracking of aluminum alloy cast rod materials during high-speed extrusion processing. There are great limitations on extrusion speed and the difficulty of forming complex extrusion sections.

[0003] The advantage of aluminum alloy in lightweight makes it have a wide range of application prospects in the automotive field. According to statistics, the average annual increase in the amount of aluminum used in each car is 4kg to 6kg. The use of aluminum alloy in automobiles can reduce its own weight, thereby reducing the energy required for the operation of the entire vehicle and increasing the single voyage, achieving the goal of energy conservation and emission reduction. When the weight of the entire vehicle is reduced by one tenth, 6-7% of fuel resources can be saved, that is, saving fuel resources, reducing greenhouse gas production, and producing recycled aluminum alloys with low carbon emissions.

[0004] However, automotive structural parts have strict requirements on material properties. Relatively high-purity electrolytic aluminum must be used for smelting and subsequent processing to ensure that it has good mechanical strength to meet the performance requirements of automotive structural parts, which leads to high carbon emissions from parts and vehicle production. In order to solve the above problems, in recent years, scientific researchers have developed low-carbon recycled aluminum alloy materials for use as automotive structural parts. For example, CN102071341A discloses a cast aluminum-silicon alloy for an engine cylinder head, wherein the chemical composition of the alloy is as follows by weight: Si: 5.0-7.0%; Cu: 3.0-4.0%; Mg: 0.2-0.4%; Mn: 0.1-0.3%; Zr: 0.10-0.20%; Ti: 0.15-0.25%; B: 0.01-0.05%; Sr: 0.02-0.09%; Re: 0.1-0.3%; Fe<0.3%; Al: balance, Re using mixed rare earth, ultimate tensile strength = 325-350MPa, elongation = 2.5-5.0%.

[0005] At present, most aluminum alloys used in automotive structural parts are 6061 aluminum alloy T6 materials prepared by smelting relatively high purity electrolytic aluminum, with a tensile strength of about 275-320 MPa, a yield strength of up to 250-280 MPa, and an elongation at break of about 10-12%. The cast aluminum silicon alloy in the prior art has good tensile strength, but its tensile properties are poor, which affects the overall extrusion processing performance and limits its application range. To this end, the inventor provides a preparation method of a low-carbon aluminum alloy and its application. Summary of the invention

[0006] In order to solve the above-mentioned existing technical problems, the inventor provides a preparation method of a low-carbon aluminum alloy and application thereof.

[0007] The preparation method of the low-carbon aluminum alloy provided by the present invention is achieved through the following technical solutions:

[0008] The preparation method of low carbon aluminum alloy comprises the following steps:

[0009] Step 1, preparation of aluminum liquid, the alloy chemical composition of the aluminum liquid is as follows by mass percentage: 0.24-0.36% Cu, 0.15-0.20% Mn, 0.8-1.2% Mg, 0.25-0.30% Zn, 0.18-0.32% Cr, 0.15-0.20% Ti, 0.4-0.8% Si, Fe≤0.5%, the balance is Al and inevitable impurities, that is, the ingredients are prepared according to the alloy chemical composition table of the above aluminum liquid, and the accurately measured recycled aluminum alloy, electrolytic aluminum block, Al-Si alloy powder, Al-Mn alloy powder, Al-Mg alloy powder, Al-Zn alloy powder, copper block, chromium block, and titanium block are heated to 960-1000° C. and melted for 0.5-2.0h to obtain aluminum liquid A;

[0010] Step 2, the aluminum liquid A is cooled to 780-800°C, a synergist is added, stirred evenly, and smelted for 2-3 hours to obtain aluminum liquid B;

[0011] The synergist at least includes surface-grafted boron nitride;

[0012] The added mass of the synergist is equal to 2-5wt% of the total mass of the aluminum liquid A;

[0013] Step 3, stirring and blowing the aluminum liquid B to remove hydrogen and impurities to obtain aluminum liquid C;

[0014] Step 4: The obtained aluminum liquid C is subjected to multi-stage filtering and slag removal treatment to obtain a finished aluminum alloy melt. The finished aluminum alloy melt is used to cast a semi-finished automotive structural part with a predetermined shape and structure. The obtained semi-finished automotive structural part is subjected to T6 heat treatment and burr grinding to obtain a low-carbon aluminum alloy.

[0015] The present invention adopts a synergist to enhance and reinforce the prepared low-carbon aluminum alloy, thereby giving it good tensile strength, yield strength and ductility, so that the prepared low-carbon aluminum alloy material can meet the material performance requirements of automobile structural parts. The use of the low-carbon aluminum alloy material in the present invention not only reduces the weight of the whole vehicle and the energy consumption of the whole vehicle operation, but also increases the single voyage of the whole vehicle.

[0016] Preferably, the recycled aluminum alloy is a recycled aluminum alloy material for automobiles.

[0017] Preferably, the base boron nitride in the surface-grafted boron nitride comprises hexagonal boron nitride nanosheets with a sheet diameter of 100-3000 nm; nano-scale metal particles are formed on the surface of the base boron nitride by a sol-gel method.

[0018] Preferably, the base boron nitride in the surface-grafted boron nitride is a mixture of hexagonal boron nitride nanosheets and boron nitride whiskers, the boron nitride whiskers have a diameter of 0.5-1 μm and a length of 20-30 μm; the boron nitride is hexagonal boron nitride nanosheets with a sheet diameter of 100-3000 nm; the nanoscale metal particles on the surface of the base boron nitride are at least one of nano-metal aluminum clusters, nano-metal magnesium clusters, nano-metal copper clusters, and nano-metal silver clusters.

[0019] Preferably, the mass ratio of hexagonal boron nitride nanosheets to boron nitride whiskers in the boron nitride matrix is ​​(75-85):(15-25).

[0020] Preferably, the synergist is composed of hexagonal boron nitride nanosheets with surface grafted nano-metal aluminum clusters, boron nitride whiskers with surface grafted nano-metal aluminum clusters, and ultrafine manganese disilicide with an average particle size of 0.1-3 microns in a mass ratio of (2-5):(2-4):(1-2).

[0021] Preferably, the synergist is composed of hexagonal boron nitride nanosheets with surface grafted nano-metal aluminum clusters, boron nitride whiskers with surface grafted nano-metal aluminum clusters, and ultrafine manganese disilicide with an average particle size of 100 nm in a mass ratio of 50:35:15.

[0022] The present invention improves the compatibility of the synergist with the aluminum alloy matrix by performing surface structure modification grafting on the synergist, and the synergist can be evenly dispersed in the aluminum alloy system through a traditional melting process, thereby playing a good toughening and reinforcing role, ensuring that the obtained low-carbon aluminum alloy material meets the performance requirements of structural parts materials for automobiles.

[0023] Preferably, the added mass of the synergist in step 2 is equal to 3.5-4.0wt% of the total mass of the aluminum liquid A.

[0024] Preferably, the ratio of the added mass of recycled aluminum alloy to the added mass of the synergist is (23-24):1.

[0025] The present invention has found through experimental research on the added mass of recycled aluminum alloy and the added mass of synergist that the mechanical strength and ductility of the prepared low-carbon aluminum alloy material are directly related to the added mass of recycled aluminum alloy and the added mass of synergist. When the ratio of the added mass of recycled aluminum alloy to the added mass of synergist is (23-24):1, the prepared low-carbon aluminum alloy material has relatively better mechanical strength and ductility. Combined with the improvement of the formula of the synergist, that is, under the premise of ensuring the mechanical strength and ductility of the low-carbon aluminum alloy material, the amount of synergist used can be reduced, thereby reducing the production cost.

[0026] The low-carbon aluminum alloy prepared by the above-mentioned low-carbon aluminum alloy preparation method is applied to the field of automobile structural parts, which can reduce the weight of the whole vehicle and the energy consumption of the whole vehicle operation, increase the range and reduce energy consumption.

[0027] In summary, the present invention has the following advantages:

[0028] 1. The low-carbon aluminum alloy prepared in the present invention has good tensile strength, yield strength and ductility, which can meet the material performance requirements of automobile structural parts, reduce the weight of the whole vehicle and the energy consumption of the whole vehicle operation, and at the same time increase the single voyage.

[0029] 2. In the present invention, the compatibility of the synergist with the aluminum alloy matrix is ​​improved by surface modification and grafting treatment of the synergist, and the synergist is evenly dispersed in the aluminum alloy system. The synergist can be evenly dispersed through a traditional melting process, which plays a good toughening and reinforcing role, thereby ensuring that the obtained low-carbon aluminum alloy material meets the material performance requirements of automotive structural parts.

[0030] 3. The present invention optimizes and improves the formula and ratio of the synergist, which can play a better toughening and strengthening role, that is, the obtained low-carbon aluminum alloy material can better meet the material performance requirements of automobile structural parts.

[0031] 4. The melting preparation process provided by the present invention is relatively simple and easy to implement industrial production. DETAILED DESCRIPTION

[0032] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0033] Example

[0034] The preparation method of low carbon aluminum alloy comprises the following steps:

[0035] Step 1, preparation of aluminum liquid, the alloy chemical composition of the aluminum liquid is as follows by mass percentage: 0.24-0.36% Cu, 0.15-0.20% Mn, 0.8-1.2% Mg, 0.25-0.30% Zn, 0.18-0.32% Cr, 0.15-0.20% Ti, 0.4-0.8% Si, Fe≤0.5%, the balance is Al and inevitable impurities, that is, the ingredients are prepared according to the above alloy chemical composition table of aluminum liquid, and the accurately measured recycled aluminum alloy, electrolytic aluminum block, Al-Si alloy powder, Al-Mn alloy powder, Al-Mg alloy powder, Al-Zn alloy powder, copper block, chromium block, and titanium block are heated to 960-1000° C. and melted for 0.5-2.0h to obtain aluminum liquid A;

[0036] The content of the recycled aluminum alloy in step 1 accounts for 65-75wt% of the total mass of the aluminum liquid A;

[0037] The recycled aluminum alloy in step one is a recycled aluminum alloy material for automobiles.

[0038] Step 2: After the aluminum liquid A is cooled to 780-800°C, a synergist is added, stirred and smelted for 2-3 hours to obtain aluminum liquid B;

[0039] The synergist at least includes surface-grafted boron nitride;

[0040] The base boron nitride in the surface grafted boron nitride comprises at least hexagonal boron nitride nanosheets with a sheet diameter of 100-3000nm, and nano-scale metal particles are formed on the surface of the base boron nitride by a sol-gel method;

[0041] Preferably, the substrate boron nitride is hexagonal boron nitride nanosheets and boron nitride whiskers, the diameter of the hexagonal boron nitride nanosheets is 100-3000nm, the diameter of the boron nitride whiskers is 0.5-1μm, and the length is 20-30μm; the nanoscale metal particles formed on the surface of the substrate boron nitride by the sol-gel method are at least one of nanometal aluminum clusters, nanometal magnesium clusters, nanometal magnesium cluster copper clusters, and nanometal silver clusters; further preferably, the mass ratio of hexagonal boron nitride nanosheets to boron nitride whiskers is (75-85):(15-25), and the nanoscale metal particles formed on the surface of the substrate boron nitride by the sol-gel method are nanometal aluminum clusters;

[0042] Preferably, the synergist is composed of hexagonal boron nitride nanosheets with surface grafted nano-metal aluminum clusters, boron nitride whiskers with surface grafted nano-metal aluminum clusters, and ultrafine manganese disilicide with an average particle size of 0.1-3 microns in a mass ratio of (2-5):(2-4):(1-2);

[0043] Industrial preferred solution: The synergist is composed of hexagonal boron nitride nanosheets with nano-metal aluminum clusters grafted on the surface, boron nitride whiskers with nano-metal aluminum clusters grafted on the surface, and ultrafine manganese disilicide with an average particle size of 100nm in a mass ratio of 50:35:15;

[0044] The added mass of the synergist is equal to 2-5wt% of the total mass of the aluminum liquid A;

[0045] Preferably, the added mass of the synergist in step 2 is equal to 3.5-4.0wt% of the total mass of the aluminum liquid A; and the ratio of the added mass of the recycled aluminum alloy to the added mass of the synergist is (23-24):1;

[0046] Step 3, stirring and blowing the aluminum liquid B to remove hydrogen and impurities to obtain aluminum liquid C;

[0047] Step 4: The obtained aluminum liquid C is subjected to multi-stage filtering and slag removal treatment to obtain a finished aluminum alloy melt. The finished aluminum alloy melt is used to cast a semi-finished automotive structural part with a predetermined shape and structure. The obtained semi-finished automotive structural part is subjected to T6 heat treatment and burr grinding treatment.

[0048] The low-carbon aluminum alloy prepared by the above-mentioned low-carbon aluminum alloy preparation method is applied to the field of automobile structural parts, which can reduce the weight of the whole vehicle and the energy consumption of the whole vehicle operation, increase the range and reduce energy consumption.

[0049] Preparation Example 1: Preparation method of hexagonal boron nitride nanosheets with nano-scale metal aluminum clusters on the surface: First, 16.8 g of aluminum nitrate nonahydrate was dissolved in a 1.5 L beaker containing 1000 mL of distilled water, a magnetic stirrer was added to the 1.5 L beaker, and the magnetic speed was adjusted to 200 rpm for 0.5 h, and then 25 g of hexagonal boron nitride nanosheets (average thickness: <100 nm; sheet diameter 1-3 μm, specific surface area 30 m2) were added to the solution at a rate of 1 g / 10 s. 2 / g, Angxing New Carbon Materials Changzhou Co., Ltd.), after the addition was completed, magnetic stirring was continued at 200rpm for 5min, and then ultrasonic dispersion treatment was performed at an ultrasonic frequency of 40kHz and a power of 800W for 20min, and then ammonia water with a concentration of 4.0wt% was added until Al 3+After complete precipitation, Al(OH)3 is formed, and magnetic stirring is continued at 200 rpm for 1 hour. After stirring, it is allowed to stand for 36 hours to age, thereby obtaining Al(OH)3 / BN binary colloid. The Al(OH)3 / BN binary colloid is washed three times with distilled water, and then filtered under reduced pressure to obtain Al(OH)3 / BN solid material. The solid material is dried at 125°C for 12 hours, and then calcined in a transfer atmosphere tube furnace. The temperature is raised to 620°C at 15°C / min in an air atmosphere and calcined for 4 hours to obtain Al2O3@BN composite powder. A hydrogen-argon mixed gas (hydrogen / argon volume ratio of 1:3) is introduced into the atmosphere tube furnace, and the temperature is maintained at 620°C for 4 hours for reduction reaction. The furnace is opened and naturally cooled to room temperature. The obtained powder is placed in a planetary ball mill and ball-milled at 120 rpm for 15 minutes to obtain hexagonal boron nitride nanosheets with a sheet diameter of 0.5-1 μm and a surface-loaded nano-scale metal aluminum cluster.

[0050] The difference between Preparation Example 2 and Preparation Example 1 is that the hexagonal boron nitride nanosheets are replaced by boron nitride whiskers.

[0051] Preparation method of boron nitride whiskers with nano-scale metal aluminum clusters loaded on the surface: first, 16.8g of aluminum nitrate nonahydrate was dissolved in a 1.5L beaker containing 1000mL of distilled water, a magnetic stirrer was added to the 1.5L beaker, and the magnetic speed was adjusted to 200rpm for 0.5h, and then 20g of boron nitride whiskers (diameter 0.5μm, length 20μm, Shanghai Xiangtian Nanomaterial Co., Ltd.) were added to the solution at an addition rate of 1g / 10s, and after the addition was completed, the magnetic stirring was continued at 100rpm for 15min, and then ultrasonic dispersion treatment was performed at an ultrasonic frequency of 40kHz and a power of 800W for 20min, and then ammonia water with a concentration of 4.0wt% was added until Al 3+ After complete precipitation, Al(OH)3 is formed, and magnetic stirring is continued at 200 rpm for 1 hour. After stirring, it is allowed to stand for 36 hours to age, thereby obtaining Al(OH)3 / BN binary colloid. The Al(OH)3 / BN binary colloid is washed three times with distilled water, and then filtered under reduced pressure to obtain Al(OH)3 / BN solid material. The solid material is dried at 125°C for 12 hours and then calcined in a transfer atmosphere tube furnace. The temperature is raised to 635°C at 15°C / min in an air atmosphere and calcined for 4.0 hours to obtain Al2O3@BN composite powder. A hydrogen-argon mixed gas (hydrogen / argon volume ratio of 1:3) is introduced into the atmosphere tube furnace, and the reduction reaction is maintained at 635°C for 4.0 hours. The furnace is opened and naturally cooled to room temperature. The obtained powder is placed in a planetary ball mill and ball-milled at 120 rpm for 15 minutes to obtain boron nitride whiskers with surface-loaded nano-scale metal aluminum clusters.

[0052] The difference between Preparation Example 3 and Preparation Example 1 is that the surface of the hexagonal boron nitride nanosheets is loaded with nano-metal aluminum clusters and nano-metal magnesium clusters.

[0053] The preparation method of hexagonal boron nitride nanosheets loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface is as follows: first, 12.4g of aluminum nitrate nonahydrate and 3.2g of magnesium nitrate hexahydrate are dissolved in a 1.5L beaker containing 1000mL of distilled water, a magnetic stirring bar is added to the 1.5L beaker, and the magnetic speed is adjusted to 200rpm for 0.5h, and then 25g of hexagonal boron nitride nanosheets are added to the solution at an addition rate of 1g / 10s. After the addition is completed, the magnetic stirring is continued at 200rpm for 5min, and then ultrasonic dispersion treatment is performed at an ultrasonic frequency of 40kHz and a power of 800W for 20min, and then ammonia water with a concentration of 4.0wt% is added until Al 3+ and Mg 2+ After complete precipitation, Al(OH)3 and Mg(OH)2 are formed, and magnetic stirring is continued at 200 rpm for 1 hour. After stirring, it is allowed to stand for 36 hours to obtain Al(OH)3+Mg(OH)2 / BN colloid. The Al(OH)3+Mg(OH)2 / BN colloid is washed three times with distilled water, and then filtered under reduced pressure to obtain Al(OH)3+Mg(OH)2 / BN solid material, which is placed at 125°C for drying for 12 hours and then calcined in a transposed atmosphere tubular furnace. In an air atmosphere, the temperature was raised to 620°C at 15°C / min and calcined for 2h, then raised to 780°C and calcined for 2h to obtain Al2O3+MgO@BN composite powder, and then a hydrogen-argon mixed gas (hydrogen / argon volume ratio of 1:3) was introduced into the atmosphere tubular furnace, and the temperature was maintained at 780°C for reduction reaction for 4h. The furnace was opened and naturally cooled to room temperature. The obtained powder was placed in a planetary ball mill and ball-milled at 120rpm for 15min to obtain hexagonal boron nitride nanosheets with surface loaded with nano-metal aluminum clusters and nano-metal magnesium clusters.

[0054] Preparation Example 4 is different from Preparation Example 2 in that the preparation method of boron nitride whiskers loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface is as follows: first, 12.4 g of aluminum nitrate nonahydrate and 3.2 g of magnesium nitrate hexahydrate are dissolved in a 1.5 L beaker containing 1000 mL of distilled water, a magnetic stirrer is added to the 1.5 L beaker, the magnetic speed is adjusted to 200 rpm for 0.5 h, and then 20 g of boron nitride whiskers are added to the solution at a rate of 1 g / 10 s. After the addition is completed, the magnetic stirring is continued at 100 rpm for 15 min, and then ultrasonic dispersion treatment is performed at an ultrasonic frequency of 40 kHz and a power of 800 W for 20 min, and then ammonia water with a concentration of 4.0 wt% is added until Al 3+ and Mg 2+After complete precipitation, Al(OH)3 and Mg(OH)2 are formed, and magnetic stirring is continued at 200 rpm for 1 hour. After the stirring is completed, it is allowed to stand for 36 hours to obtain Al(OH)3+Mg(OH)2 / BN colloid; the Al(OH)3+Mg(OH)2 / BN colloid is washed three times with distilled water, and then the Al(OH)3+Mg(OH)2 / BN solid material is obtained by vacuum filtration, which is placed at 125°C for drying for 12 hours and then calcined in a transposed atmosphere tubular furnace. Treatment, in an air atmosphere, the temperature was increased to 635 ° C at 15 ° C / min and calcined for 2 h, and then the temperature was increased to 780 ° C and calcined for 2 h to obtain Al2O3 + MgO @ BN composite powder, and then a hydrogen-argon mixed gas (hydrogen / argon volume ratio of 1:3) was introduced into the atmosphere tubular furnace, and the temperature was maintained at 780 ° C for reduction reaction for 4 h. The furnace was opened and naturally cooled to room temperature. The obtained powder was placed in a planetary ball mill and ball-milled at 120 rpm for 15 min to obtain boron nitride whiskers with surface loaded with nano-metal aluminum clusters and nano-metal magnesium clusters.

[0055] Preparation Example 5 is different from Preparation Example 1 in that the preparation method of boron nitride with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface is as follows: first, 12.4g of aluminum nitrate nonahydrate and 3.2g of magnesium nitrate hexahydrate are dissolved in a 1.5L beaker containing 1000mL of distilled water, a magnetic stirrer is added to the 1.5L beaker, and the magnetic speed is adjusted to 200rpm for 0.5h, and then 10g of boron nitride whiskers and 15g of hexagonal boron nitride nanosheets are added to the solution at an addition rate of 1g / 10s. After the addition is completed, the magnetic stirring is continued at 100rpm for 15min, and then ultrasonic dispersion treatment is performed at an ultrasonic frequency of 40kHz and a power of 800W for 20min, and then ammonia water with a concentration of 4.0wt% is added until Al 3+ and Mg 2+ After complete precipitation, Al(OH)3 and Mg(OH)2 are formed, and magnetic stirring is continued at 200 rpm for 1 hour. After stirring, it is allowed to stand for 36 hours to obtain Al(OH)3+Mg(OH)2 / BN colloid. The Al(OH)3+Mg(OH)2 / BN colloid is washed three times with distilled water, and then filtered under reduced pressure to obtain Al(OH)3+Mg(OH)2 / BN solid material, which is dried at 125°C for 12 hours and then calcined in a transposed atmosphere tubular furnace. , the temperature was raised to 635°C in an air atmosphere at 15°C / min and calcined for 2h, and then the temperature was raised to 780°C and calcined for 2h to obtain Al2O3+MgO@BN composite powder, and then a hydrogen-argon mixed gas (hydrogen / argon volume ratio of 1:3) was introduced into the atmosphere tubular furnace, and the temperature was maintained at 780°C for reduction reaction for 4h. The furnace was opened and naturally cooled to room temperature. The obtained powder was placed in a planetary ball mill and ball-milled at 120rpm for 15min to obtain a boron nitride mixed enhancer with surface loaded nano-metal aluminum clusters and nano-metal magnesium clusters.

[0056] The difference between Preparation Example 6 and Preparation Example 5 is that the preparation method of boron nitride with nano-metal silver clusters, nano-metal aluminum clusters and nano-metal magnesium clusters on the surface is as follows: first, 1.5g of silver nitrate, 9.8g of aluminum nitrate nonahydrate and 3.2g of magnesium nitrate hexahydrate are dissolved in a 1.5L beaker containing 1000mL of distilled water, a magnetic stirrer is added to the 1.5L beaker, the magnetic speed is adjusted to 200rpm for 0.5h, and then 10g of boron nitride whiskers and 15g of hexagonal boron nitride nanosheets are added to the solution at an addition rate of 1g / 10s. After the addition is completed, magnetic stirring is continued at 100rpm for 20min, and then ultrasonic dispersion treatment is performed at an ultrasonic frequency of 40kHz and a power of 800W for 25min, and then ammonia water with a concentration of 4.0wt% is added until Ag is dissolved. + 、Al 3+ and Mg 2+ After complete precipitation, AgOH, Al(OH)3 and Mg(OH)2 were formed, and the mixture was stirred magnetically at 200 rpm for 1 hour. After stirring, the mixture was aged for 36 hours to obtain AgOH, Al(OH)3+Mg(OH)2 / BN colloid. The AgOH, Al(OH)3+Mg(OH)2 / BN colloid was washed three times with distilled water, and then filtered under reduced pressure to obtain AgOH, Al(OH)3+Mg(OH)2 / BN solid material. The solid material was dried at 125°C for 12 hours, and then calcined in a transfer atmosphere tube furnace. The temperature was raised to 450°C at a rate of 15°C / min under atmosphere and calcined for 1h, then raised to 635°C and calcined for 1h, and then raised to 780°C and calcined for 2h to obtain AgO+Al2O3+MgO@BN composite powder, and then a hydrogen-argon mixed gas (hydrogen / argon volume ratio of 1:3) was introduced into the atmosphere tubular furnace, and the reduction reaction was maintained at 650°C for 4h. The furnace was opened and naturally cooled to room temperature. The obtained powder was placed in a planetary ball mill and ball-milled at 120rpm for 15min to obtain a boron nitride mixed enhancer with surface loaded nano-metal silver clusters, nano-metal aluminum clusters and nano-metal magnesium clusters.

[0057] Embodiment 1: A method for preparing a low carbon aluminum alloy, comprising the following steps:

[0058] Step 1, preparation of aluminum liquid, the alloy chemical composition of the aluminum liquid is as follows by mass percentage: 0.30% Cu, 0.15% Mn, 1.0% Mg, 0.25% Zn, 0.25% Cr, 0.15% Ti, 0.65% Si, Fe≤0.5%, and the balance is Al and inevitable impurities, that is, according to the above alloy chemical composition table of aluminum liquid, the ingredients are prepared, and the accurately measured recycled aluminum alloy (automotive recycled aluminum alloy material, provided by Hukou Qimei Waste Aluminum Co., Ltd.), electrolytic aluminum block, Al-Si alloy powder, Al-Mn alloy powder, Al-Mg alloy powder, Al-Zn alloy powder, copper block, chromium block, and titanium block are heated to 980° C. for melting and then ultrasonically stirred for 1.0 h to obtain aluminum liquid A;

[0059] The content of the recycled aluminum alloy in step 1 accounts for 65wt% of the total mass of the aluminum liquid A;

[0060] Step 2: After the aluminum liquid A is cooled to 780°C, a synergist is added, wherein the synergist is a mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5, and the amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 is 2wt% of the total mass of the aluminum liquid A, and the aluminum liquid B is obtained by uniformly smelting with ultrasonic stirring for 2.0h;

[0061] Step 3, stirring and blowing the aluminum liquid B to remove hydrogen and impurities to obtain aluminum liquid C;

[0062] Step 4: The obtained aluminum liquid C is subjected to multi-stage filtration and slag removal to obtain a finished aluminum alloy melt. The finished aluminum alloy melt is used to cast a semi-finished automotive structural part with a predetermined shape and structure. The obtained semi-finished automotive structural part is subjected to T6 heat treatment: the temperature is increased to 525°C at 5°C / min and solution treatment is performed for 10 hours. After water quenching to room temperature, artificial aging treatment is performed: the temperature is increased to 175°C at 2°C / min and kept warm for 6 hours. The furnace is opened and cooled to room temperature, and the burrs are polished to obtain the obtained part.

[0063] The difference between Example 2 and Example 1 is that the amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 3wt% of the total mass of the aluminum liquid A.

[0064] The difference between Example 3 and Example 1 is that the amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 4wt% of the total mass of the aluminum liquid A.

[0065] The difference between Example 4 and Example 1 is that the amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 5wt% of the total mass of the aluminum liquid A.

[0066] The difference between Example 5 and Example 1 is that the content of the recycled aluminum alloy in step 1 accounts for 65wt% of the total mass of the aluminum liquid A. The amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 2.65wt% of the total mass of the aluminum liquid A.

[0067] The difference between Example 6 and Example 1 is that the content of the recycled aluminum alloy in step 1 accounts for 70wt% of the total mass of the aluminum liquid A. The amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 2.90wt% of the total mass of the aluminum liquid A.

[0068] The difference between Example 7 and Example 1 is that the content of the recycled aluminum alloy in step 1 accounts for 75wt% of the total mass of the aluminum liquid A. The amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 3.10wt% of the total mass of the aluminum liquid A.

[0069] The difference between Example 8 and Example 6 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with surface-loaded nanoscale metal aluminum clusters in Preparation Example 1 and boron nitride whiskers with surface-loaded nanoscale metal aluminum clusters in Preparation Example 2 in a mass ratio of 1:1.

[0070] The difference between Example 9 and Example 6 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with surface-loaded nanoscale metal aluminum clusters in Preparation Example 1 and boron nitride whiskers with surface-loaded nanoscale metal aluminum clusters in Preparation Example 2 in a mass ratio of 4:1.

[0071] The difference between Example 10 and Example 6 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with surface-loaded nanoscale metal aluminum clusters in Preparation Example 1 and boron nitride whiskers with surface-loaded nanoscale metal aluminum clusters in Preparation Example 2 in a mass ratio of 7:1.

[0072] The difference between Example 11 and Example 6 is that the enhancer in step 2 is composed of hexagonal boron nitride nanosheets with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 3 and boron nitride whiskers with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 4 in a mass ratio of 4:1.

[0073] The difference between Example 12 and Example 6 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with nano-metal aluminum clusters loaded on the surface in Preparation Example 1 and boron nitride whiskers with nano-metal aluminum clusters and nano-metal magnesium clusters loaded on the surface in Preparation Example 4 in a mass ratio of 4:1.

[0074] The difference between Example 13 and Example 6 is that the synergist in step 2 is composed of the boron nitride mixed synergist with surface loaded nano-metal aluminum clusters and nano-metal magnesium clusters in Preparation Example 5 and ultrafine manganese disilicide with an average particle size of 0.1 micron (Nangong Jiuxin New Material Technology Co., Ltd.) in a mass ratio of 9:1.

[0075] The difference between Example 14 and Example 3 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with nano-metal aluminum clusters loaded on the surface in Preparation Example 1, boron nitride whiskers with nano-metal aluminum clusters loaded on the surface in Preparation Example 2, and ultrafine manganese disilicide with an average particle size of 1-3 microns (Ningbo Luofei Nanotechnology Co., Ltd.) in a mass ratio of 5:4:1.

[0076] The difference between Example 15 and Example 6 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with surface-loaded nano-metal aluminum clusters in Preparation Example 1, boron nitride whiskers with surface-loaded nano-metal aluminum clusters in Preparation Example 2, and ultrafine manganese disilicide with an average particle size of 1-3 microns in a mass ratio of 1:1:1.

[0077] The difference between Example 16 and Example 6 is that the synergist in step 2 is composed of hexagonal boron nitride nanosheets with surface-loaded nano-metal aluminum clusters in Preparation Example 1, boron nitride whiskers with surface-loaded nano-metal aluminum clusters in Preparation Example 2, and ultrafine manganese disilicide with an average particle size of 1-3 microns in a mass ratio of 50:35:15.

[0078] The difference between Comparative Example 1 and Example 1 is that: in step 2, after the aluminum liquid A is cooled to 780°C, a synergist is added, the synergist is hexagonal boron nitride nanosheets, and the amount of hexagonal boron nitride nanosheets added is equal to 2wt% of the total mass of the aluminum liquid A. The aluminum liquid B is obtained by stirring and smelting evenly for 2.0h.

[0079] The difference between Comparative Example 2 and Example 1 is that: in step 2, after the aluminum liquid A is cooled to 780°C, a synergist is added, the synergist is boron nitride whisker, and the amount of boron nitride whisker added is equal to 2wt% of the total mass of the aluminum liquid A. The aluminum liquid B is obtained by stirring and smelting evenly for 2.0h.

[0080] The difference between Comparative Example 3 and Example 1 is that: in step 2, after the aluminum liquid A is cooled to 780°C, a synergist is added, the synergist is hexagonal boron nitride whisker and boron nitride whisker, the mass ratio of hexagonal boron nitride whisker to boron nitride whisker is 4:1, and the amount of the synergist added is equal to 2wt% of the total mass of the aluminum liquid A. The aluminum liquid B is obtained by stirring and smelting evenly for 2.0h.

[0081] The difference between Comparative Example 4 and Example 1 is that the amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 1wt% of the total mass of the aluminum liquid A.

[0082] The difference between Comparative Example 5 and Example 1 is that the amount of the mixed boron nitride synergist loaded with nano-metal aluminum clusters and nano-metal magnesium clusters on the surface in Preparation Example 5 in step 2 is equal to 6wt% of the total mass of the aluminum liquid A.

[0083] Performance test: 1. The tensile strength, elongation and yield strength are measured by WDW-50D universal tensile testing machine according to GB / T 228.1-2010. 2. The corrosion resistance is evaluated according to GB / T 22639-2008 standard.

[0084] Table 1: Test parameters of low carbon aluminum alloys in Examples 1-18 and Comparative Examples 1-8

[0085]

[0086] It can be seen from Example 1, Examples 2-4 and Comparative Examples 4-5 and Table 1 that the added mass of the synergist is preferably equal to 2-5wt% of the total mass of the aluminum liquid A. Preferably, the added mass of the synergist is equal to 3-4wt% of the total mass of the aluminum liquid A, which can ensure the tensile strength, yield strength and ductility of the prepared low-carbon aluminum alloy, reduce production costs and meet the purpose of low-carbon and environmentally friendly production.

[0087] Combining Example 1 and Examples 7-9 with Table 1, it can be seen that the ratio of the added mass of the recycled aluminum alloy to the added mass of the synergist is (23-24):1, and the tensile strength, yield strength and ductility of the prepared low-carbon aluminum alloy are better.

[0088] Combining Example 6, Examples 8-16 and Comparative Examples 1-3 and Table 1, it can be seen that the hexagonal boron nitride nanosheets grafted with nanometal clusters on the surface and the boron nitride whiskers grafted with nanometal clusters on the surface are compounded as synergists, and the tensile strength, yield strength and ductility of the prepared low-carbon aluminum alloy are better. Preferably, the mass ratio of the hexagonal boron nitride nanosheets grafted with nanometal clusters on the surface and the boron nitride whiskers grafted with nanometal clusters on the surface is 4:1.

[0089] Combining Example 6, Examples 8-16 and Comparative Examples 1-3 and Table 1, it can be seen that the synergist formed by compounding hexagonal boron nitride nanosheets grafted with nano-metal clusters, boron nitride whiskers grafted with nano-metal clusters, and ultrafine manganese disilicide with an average particle size of 0.1-3 microns has better tensile strength, yield strength, and ductility of the low-carbon aluminum alloy prepared. Preferably, the hexagonal boron nitride nanosheets grafted with nano-metal clusters, boron nitride whiskers grafted with nano-metal clusters, and ultrafine manganese disilicide with an average particle size of 0.1-3 microns are in a mass ratio of (2-5):(2-4):(1-2).

[0090] It can be seen from Example 6, Examples 8-16 and Comparative Examples 1-3 and Table 1 that the tensile strength, yield strength and ductility of the low-carbon aluminum alloy prepared by using ultrafine manganese disilicide with an average particle size of 0.1 micrometers and a synergist of hexagonal boron nitride nanosheets with surface grafted nano-metal clusters and boron nitride whiskers with surface grafted nano-metal clusters are relatively better, but the overall production cost is relatively high.

[0091] It can be seen from Example 6, Examples 8-16 and Comparative Examples 1-3 and Table 1 that the synergist composed of hexagonal boron nitride nanosheets with surface grafted nano-metal clusters and boron nitride whiskers with surface grafted nano-metal clusters and ultrafine manganese disilicide with an average particle size of 100 nm in a mass ratio of 50:35:15 is a compound of the low-carbon aluminum alloy prepared with relatively better tensile strength, yield strength and ductility.

[0092] In summary, the low-carbon aluminum alloy prepared in the present invention has good tensile strength, yield strength and ductility, which can meet the material performance requirements of automobile structural parts, reduce the weight of the whole vehicle and the energy consumption of the whole vehicle operation, and at the same time increase the single voyage range.

[0093] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A method for preparing a low carbon aluminum alloy, characterized in that: The following steps are involved: Step 1, preparation of aluminum liquid, the alloy chemical composition of the aluminum liquid is as follows by mass percentage: 0.24-0.36% Cu, 0.15-0.20% Mn, 0.8-1.2% Mg, 0.25-0.30% Zn, 0.18-0.32% Cr, 0.15-0.20% Ti, 0.4-0.8% Si, Fe≤0.5%, the balance is Al and inevitable impurities, that is, according to the alloy chemical composition of the above aluminum liquid, the ingredients are prepared, and the accurately measured recycled aluminum alloy, electrolytic aluminum block, Al-Si alloy powder, Al-Mn alloy powder, Al-Mg alloy powder, Al-Zn alloy powder, copper block, chromium block, and titanium block are heated to 960-980° C. and melted for 0.5-2.0h to obtain aluminum liquid A; Step 2, the aluminum liquid A is cooled to 780-800°C, a synergist is added, stirred evenly, and smelted for 2-3 hours to obtain aluminum liquid B; The synergist at least includes surface-grafted boron nitride; The added mass of the synergist is equal to 2-5wt% of the total mass of the aluminum liquid A; Step 3, stirring and blowing the aluminum liquid B to remove hydrogen and impurities to obtain aluminum liquid C; Step 4: The obtained aluminum liquid C is subjected to multi-stage filtering and slag removal treatment to obtain a finished aluminum alloy melt, and the finished aluminum alloy melt is used for casting to obtain a semi-finished automobile structural part with a predetermined shape and structure, and the obtained semi-finished automobile structural part is subjected to T6 heat treatment and burr grinding treatment to obtain a low-carbon aluminum alloy; The synergist is composed of hexagonal boron nitride nanosheets with nano-metal aluminum clusters grafted on the surface, boron nitride whiskers with nano-metal aluminum clusters grafted on the surface, and ultrafine manganese disilicide with an average particle size of 0.1-3 microns in a mass ratio of (2-5):(2-4):(1-2).

2. The method for preparing a low carbon aluminum alloy according to claim 1, characterized in that: The recycled aluminum alloy is a recycled aluminum alloy material for vehicles.

3. The method for preparing a low carbon aluminum alloy according to claim 1, characterized in that: The synergist is composed of hexagonal boron nitride nanosheets with nano-metal aluminum clusters grafted on the surface, boron nitride whiskers with nano-metal aluminum clusters grafted on the surface, and ultrafine manganese disilicide with an average particle size of 100nm in a mass ratio of 50:35:

15.

4. The method for preparing a low carbon aluminum alloy according to claim 1, characterized in that: The added mass of the synergist in step 2 is equal to 3.5-4.0wt% of the total mass of the aluminum liquid A.

5. The method for preparing a low carbon aluminum alloy according to claim 1, characterized in that: The ratio of the added mass of the recycled aluminum alloy to the added mass of the synergist is (23-24):

1.

6. The low-carbon aluminum alloy prepared by the method for preparing the low-carbon aluminum alloy according to any one of claims 1 to 5 is used in the field of automobile structural parts.

Citation Information

Patent Citations

  • Cast aluminum-silicon alloy for engine cylinder head and heat treatment process

    CN102071341A

  • Method for preparing regenerated wrought aluminum alloy from scrap aluminum alloy

    CN113234949A

  • Aluminum-based silicon carbide composite material and injection molding preparation process

    CN118064812A

  • Aluminum-based silicon carbide material with mirror surface effect and preparation process thereof

    CN118417568A

  • Free-machining aluminum alloy

    US20120093682A1